سورة النساء و ما فيها من المجاز المرسل: SURAT AN-NISA’ AND HIS RELATED O - Aulia Fitri (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
مستخلص البحث: يهدف هذا البحث لكشف الكلمات المجاز المرسل في سورة النساء من القرآن الكريم. أما الطرق المستعملة في هذا البحث هي طريقة البحث الكيفي لأنه يتعلق بجملة والمفردات. وطريقة جمع البيانات هي طريقة البحث المكتبي والبحث التحليلي عن الكلمات المجاز المرسل. أما نتيجة البحث هي تحليل من علاقات المجاز المفرد المرسل عدده 17 وفيها أسلوب المجاز المفرد الكلمات المفتاحية: المجاز المرسل، البلاغية، سورة النساء Abstract: This research aims to reveal the metaphorical words sent in Surat Al-Nisa from the Holy Quran. The methods used in this research are the qualitative research method because it is related to sentences and vocabulary. The method of data collection is the method of desk research and analytical search for metaphorical words sent. As for the result of the research, it is an analysis of the relationships of the singular metaphor sent number 17, and it includes the style of the singular metaphor.Keywords: Majaz mursal, rhetorically (balaghiyah), Surat An nisa